ANTHROPOPHAGIC ANALYSIS IN CAETANO VELOSO’S SUPERBACANA MUSIC - Fernandes de Oliveira, Aciomar (Revista Gênero e Interdisciplinaridade, 2025)
This article examines the anthropophagic production methodology used by members of the group “Tropicália”, giving a new look to European ideas and models without subordinating themselves to the dichotomies between national and foreign. Representations that resonate in various artistic, social and political manifestations of the time. For this research, the discography of Caetano Veloso’s first album (1968) entitled “Caetano Veloso” was explored. This research was based on audiovisual recordings available in the public domain, interviews published in periodicals and online addresses, the limited official bibliography and the scarce related academic works. The theoretical contribution focused on authors who reflected on different cultural manifestations, especially in South America. Among them, Augusto de Campos, Celso Faveretto, Amador Ribeiro Neto, Jorge Caê Rodrigues, Luiz Tatit, Severo Sarduy and Caetano Veloso. The objective is to understand the manifestations of anthropophagy in Caetano Veloso’s work “Superbacana”. In this way, the presence of some dualisms was discovered, usually hierarchized from the point of view of art and which, in the case of this singer, were suppressed, giving way to one of the most striking attributes of the movement, experimentalism.